Reintroducing the GeoNames that features the land and water near the Montufar and Bingay Points in Prieto Diaz, Sorsogon, Philippines - Abante, Ana Marie R. (International Journal of Computing Sciences Research, 2022)
Purpose – The paper aims to generate analytical data to reintroduce the geographic naming based on the existing coastwise feature names as part of contextualizing the ecosystem relative to risk reality phenomena that are based on the actual land and water uses in the study area. Method – ArcGIS platform was used to assess the following: (i) coastwise feature names based on the Special Report of the United States Board of Geographic Names Relating to the Geographic Names in the Philippine Island, (ii) Topographical features and feature names, (iii) politico-administrative  and planning subdivisions, (iv) income classification of the study area, (v) natural and physical map features of the study area, (vi) disaster risk reality phenomenon, (vii) The Agta IPs environmental and Disaster Risk Reduction Practices relative to the ecosystem and actual uses of land and water in the study area Results  – Coastwise feature naming describes the physical environment that features the mountain, river, historical, cultural, or events being named, etc. The Coastwise feature names are essential in improving and promoting eco-tourism activities on the coast of Prieto Diaz as the home of the indigenous people who traditionally settle and move to another settlement merely remaining speaking their mother tongue "Agta Tabangnon and Bicol Sorsogon''.  Although the income classification of Prieto Diaz is low, during the COVID-19 lockdown the locally produced food supply was sufficient to feed Prieto Diaznon. This implies that the coping capacity during pandemic somehow hinted that the land and water utilization remain stable municipal wide. It generally implies the friendliness of Prieto Diaznon which resembles the indigenous people's friendliness to the environment before the Spaniards colonization. The natural resources are generally conserved and protected although some built-up areas were impacted by the calamities and natural hazards. But in terms of disaster risk reality was calculated to be 92% which means the study area is somewhat resilient to resilient municipalities. The remaining 8% are areas mostly located in low-lying and coastal areas. Conclusion – The coastwise feature names relating to the geographic names in the Philippine Islands remain in use for coastal directions, research to monitor sedimentation significant in assessing the general development of a regional understanding of the vegetation and climate dynamics, and weather forecasts. This study concludes that the coastwise feature names or geographic names are significant to characterize the risk or resiliency realities of the old barrios up to the present barangays. Furthermore, the coastwise feature names relating to the geographic names in the Philippine Islands remain useful to attract more tourists and researchers to visit a place virtually or on-site during and after the COVID-19 pandemic. Recommendations – Reintroduction of the geographic names by way of contextualization risk or resilience reality theory of Abante (2021a;2020a) and incorporating the of the Popper (1978)theory on "world of contents of thought", Meiring (1993) theory on 'place names', and Quine (1953) cited the Strawson's logical theory of reference on backing the naming with descriptions can also reintroduce a place starting from the 'VisitangDaan' myth up to the present barangays via internet especially during the new normal after COVID-19 pandemic to strengthen linkages and trading.